HUBUNGAN ANTARA PERSEPSI MASYARAKAT TERHADAP PROGRAM “WARGA PEDULI AIDS” DENGAN PERILAKU PENCEGAHAN PENULARAN HIV/AIDS DI KELURAHAN PETERONGAN, KOTA SEMARANG - Nizar Ferdian (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
HIV / AIDS is a health problem that spread rapidly through sex, injecting drugs or blood transfusions. Government and society should have a good cooperation to control HIV/AIDs cases. One form of this cooperative effort is the program Warga Peduli AIDS (WPA). This research subjected to Peterongan Village community because in this village are WPA, and also there was some prostitution bussiness. The purpose of this research is to analyze the relationship between subject’s perception of the “Warga Peduli AIDS” program with preventive action of HIV/AIDS’s transmission in Peterongan. This research use quantitative with cross sectional approach. The population of this research is Peterongan Village community with 8245 people and the samples taken as many as 105 people using accidental sampling technique. Sources of research data using primary data and secondary data. This research use univariate and bivariate data analysis with Chi Square test (significance level 0.05). 50.5% respondent’s age is ≥ 44 years and respondents who have a job is 56%. The majority of respondent’s income is less than the minimum wage (72.4%) and respondents with low education levels is 64.8%. Respondents with high perceived susceptibility is 69.5%, 66,7% respondent have high perceived seriousness, 61.9% have high perceived benefit and 50.5% have high perceived barrier. Chi Square test results showed that the variables age, level of education, knowledge, perceived susceptibility, perceived seriousness, and the perceived benefit of having a relationship with the preventive behavior of HIV / AIDS transmission (p<0,05). Economic income and perceived barrier have no significant relationship with the preventive behavior of HIV / AIDS transmission.